Biomarkers for early diagnosis of sepsis-associated acute kidney injury - GE Xin (Zhongguo linchuang yanjiu)
Sepsis-associated acute kidney injury (SA-AKI) is a heterogeneous syndrome caused by direct mechanisms of sepsis or indirect mechanisms induced by sepsis treatment, leading to kidney damage. Current research of SA-AKI focuses on the application of novel diagnostic biomarkers, including proenkephalin A 119-159, soluble thrombomodulin, hepcidin, urinary angiotensinogen, monocyte chemotactic protein-1, neutrophil gelatinase-associated lipocalin, cystatin C, kidney injury molecule-1, liver-type fatty acid-binding protein, and cell cycle arrest proteins. These biomarkers are related to the pathogenesis of SA-AKI. This paper summarizes the biological functions, basic and clinical research status of these early diagnostic markers, and their role in the treatment of critically ill SA-AKI patients, aiming to assist in the early identification, diagnosis, and treatment of SA-AKI in clinical practice.